EFFECT OF TAPIOCA FLOUR SUBSTITUTION WITH DURIAN SEEDS FLOUR (Durio zibethinus Murr) ON QUALITY OF SNAKEHEAD (Channa striata) FISH BALL VARIOUS COLOR - Muhammad Iqbal Harikhman; Syahrul Syahrul; Suardi Loekman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe purpose of this study was to obtain the selected percentage of tapioca flour substitution with durian seeds flour in the manufacture of snakehead fish ball various color. The method used in this study was the experimental method that was processing the snakehead fish ball of various color substituted tapioca flour with durian seed flour, the design used was a Completely Randomized Design (CRD) non factorial by comparing consumer acceptance from preliminary research result that was six levels of treatment substituted tapioca flour with durian seeds flour B0 100% : 0%, B1 80% : 20%, B2 60% : 40%, B3 40% : 60%, B4 20% : 80%, B5 0% : 100%. The most preferred panelists were on B2 treatment 60% : 40%. And then the B2 treatment of preliminary used as the main research, which was given three natural dyes in the form of red yeast rice (Monascus purpureus), carrot (Daucus carrota), and sweet leaf (Sauropus androgynus) with 10% concentrations of each. Based on the results of research that the treatment of 60% trapioca flour and 40% durian seeds flour with 10% dyes of red yeast rice (Monascus purpureus) was the best quality with the proximate value of water content 65.37%, protein content 14.28%, and fiber content 9.75%. Keywords: durian seeds flour, fishball various colour,snakehead, substitution